Influence of lamb fattening method and weight standard on carcass and meat quality - Borys B.; Janicki B. (Production systems and product quality in sheep and goats, 2001)
In two experiments carried out on a total of 64 ewe- and ram-lambs, the influence of the fattening method (intensive and semi-intensive) and weight standards on carcass quality and muscle tissue quality and composition was investigated. Both, fattening methods and weight standards significantly influenced slaughter performance, fatness indices, the results of carcass classification according to the conformation and musculature, as well as according to the fatness in the case of the weight standard. All values were higher in intensive fattening and in higher weight standards. No significant influence on muscle tissue composition and quality was observed, including the profile of fatty acids and the cholesterol content. Although the weight standards were lower for ewe-lambs than ram-lambs, the fatness of the ewes' carcasses was higher, but there were no significant differences in meat composition and quality.
Meeting of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1999/09/23-25, Molina de Segura-Murcia (Spain)